Loss of all three APP family members during development impairs synaptic function and plasticity, disrupts learning, and causes an autism‐like phenotype. (19th May 2021) - Steubler, Vicky; Erdinger, Susanne; Back, Michaela K; Ludewig, Susann; Fässler, Dominique; Richter, Max; Han, Kang; Slomianka, Lutz; Amrein, Irmgard; von Engelhardt, Jakob; Wolfer, David P; Korte, Martin; et al.
Abstract: The key role of APP for Alzheimer pathogenesis is well established. However, perinatal lethality of germline knockout mice lacking the entire APP family has so far precluded the analysis of its physiological functions for the developing and adult brain. Here, we generated conditional APP/APLP1/APLP2 triple KO (cTKO) mice lacking the APP family in excitatory forebrain neurons from embryonic day 11.5 onwards. NexCre cTKO mice showed altered brain morphology with agenesis of the corpus callosum and disrupted hippocampal lamination. Further, NexCre cTKOs revealed reduced basal synaptic transmission and drastically reduced long‐term potentiation that was associated with reduced dendritic length and reduced spine density of pyramidal cells. With regard to behavior, lack of the APP family leads not only to severe impairments in a panel of tests for learning and memory, but also to an autism‐like phenotype including repetitive rearing and climbing, impaired social communication, and deficits in social interaction. Together, our study identifies essential functions of the APP family during development, for normal hippocampal function and circuits important for learning and social behavior. SYNOPSIS: Despite the key role of the amyloid precursor protein APP for Alzheimer pathogenesis its physiological functions remained poorly understood. Here, we generated forebrain specific triple knockout mice (cTKOs) lacking APP and the two related APLPs during embryonic development to study the role of the APP gene family for brain morphology, synaptogenesis, synaptic plasticity and behavior. Lack of the APP family impairs lamination of the hippocampus. Lack of the APP family impairs neuronal morphology and spine density of hippocampal neurons. Lack of the APP family impairs basal synaptic transmission and leads to severely reduced LTP. Lack of the APP family disrupts learning and leads to core Autism‐like behaviors. The APP family is required for networks mediating learning and social behavior. Abstract : Forebrain specific triple knockout mice lacking APP and the two related APLPs show features of autism‐like behavior including altered social communication and interaction.